1969
DOI: 10.1111/j.1365-2621.1969.tb14364.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Meat Tenderness. 7. Changes in the Fine Structure of Meat During Aging

Abstract: SUMMARY— During the aging of fiber pieces prepared from bovine sternomandibularis muscles, a loss of adhesion occurs between adjacent myofibrils. This is evidenced by increased readiness of fiber pieces to distintegrate into individual myofibrils during a period of standard disruption. Alterations also appear within the myofibrils themselves in the regions of the Z lines, sometimes leading to the apparent dissolution of this structure. Ethylenediamine tetraacetate present in the suspensions during storage not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
2

Year Published

1970
1970
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(76 citation statements)
references
References 16 publications
5
69
0
2
Order By: Relevance
“…The fragmentation of myofibrils prepared from post-mortem muscle has been observed previously (Davey and Gilbert, 1969;Henderson, 1968;Stromer and Goll, 1967a;Takahashi et al, 1567) and is generally attributed to weakening at the Z-line. The pre servation effect of added EDTA or EGTA on myofibrillar structure is quite remarkable since Henderson (1968) has shown that myofibrils prepared from rabbit muscle stored in air for 4 hours at 37° are fragmented and have no Z-lines.…”
Section: Time (Hr)supporting
confidence: 55%
See 1 more Smart Citation
“…The fragmentation of myofibrils prepared from post-mortem muscle has been observed previously (Davey and Gilbert, 1969;Henderson, 1968;Stromer and Goll, 1967a;Takahashi et al, 1567) and is generally attributed to weakening at the Z-line. The pre servation effect of added EDTA or EGTA on myofibrillar structure is quite remarkable since Henderson (1968) has shown that myofibrils prepared from rabbit muscle stored in air for 4 hours at 37° are fragmented and have no Z-lines.…”
Section: Time (Hr)supporting
confidence: 55%
“…This fragmentation of post-mortem myofibrils occurs primarily at the Z-line, which suggests that post-mortem myofibrils are weakened at this point so that they break or rupture during the homogenization pro cedure used in myofibril preparation. Recently, Davey and Gilbert (1969) have observed that Z-line in post-mortem bovine muscle may be removed from the myofibril altogether and that adjacent myofibrils appear to lose their affinity for each other.…”
Section: Umentioning
confidence: 99%
“…The addition of EDTA decreased the fluorescence intensity against Ac-X 1 -MCA and Ac-Ala-Phe-MCA. On the basis on Davey's report, 20) which suggests that EDTA inhibits the degradation of Z lines by chelating calcium, it was hypothesized that the reaction of these substrates might involve calpains, a calcium-dependent protease. It is known that cathepsin B reacts specifically with the substrate Z-Arg-Arg-MCA or Z-Phe-Arg-MCA, 21) and that cathepsin L reacts specifically with the substrate Z-Phe-Arg-MCA.…”
Section: Discussionmentioning
confidence: 99%
“…The second is a weakening of myofibrils themselves, resulting in a breaking in I band region. According to the recent investigations on so called meat aging, [8][9] this is a commonly encountered phenomenon. However, the change which occurs during the jellification of tuna meat must be more drastic than that occurring during meat aging, and likely associated with a disintegration of connective tissue or sarcolemma.…”
Section: Methodsmentioning
confidence: 99%